MAKNA OPTIMISME DALAM IKLAN POLITIK “WUJUDKAN MIMPI BERSAMA JOKOWI-JK” (Analisis Semiotika Saussure Pada Scene Yang Menunjukkan Tagline JOKOWI-JK ADALAH KITA) - Indah Hapsari; Lasmery RM Girsang (SEMIOTIKA: Jurnal Komunikasi, 2015)
The aim of this study was to determine the meaning of the optimism contained in political advertising "Realize Dream Together Jokowi-JK" through the analysis of the signs of verbal and non-verbal contained in the advertisement. The method used in this research is descriptive qualitative study of semiotic analysis of Ferdinand de Saussure. Selected as a research method because semiotics can provide ample scope for interpretation to a study, in this study the ads "Realize Dream Together Jokowi-JK", so as to reveal the meaning of the optimism contained in the advertisement. The data in this study is qualitative data (data that is without numbers - numbers or numbers), so that data are substantive categories which are then interpreted by reference, references, and references - scientific reference. In the data analysis, the authors use elements of semiotics De Saussure to assess any signs contained in the advertisement, among others; signifier (markers) and the signified (signified); (2) form (shape) and content (content); (3) langue (language) and parole (speech, speech); (4) synchronic (synchronous) and diachronic (diachronic); and (5) syntagmatic (syntagmatic) and associative (paradigmatic). The relationship between these elements is analyzed into a significance of meaning that arise. From the analysis has been carried out, political advertising "Realize Dream Together Jokowi-JK" presents many social values in terms of both visual and audiovisual. The impression of the views of researchers considered a success because it can grab the sympathy of the public. Optimism is what hopefully will be able to unite all the people of Indonesia to jointly build the nation. Keywords: Semiotic, Politic Ad, Optimism meaning